Development of resilient friction beams and application to moment-resisting frames. (January 2022) - Huang, Xiaogang; Zhou, Xuhong; Wang, Yuhang; Zhu, Ronghua
Abstract: This paper proposes the concept of resilient friction beams (RFBs) and investigates how RFBs can be economically implemented in moment-resisting frames (MFs) to improve seismic performance. The RFBs mainly consist of two T-shaped beams and four cap plates, resulting in a cost-effective configuration that employs less steel than previous self-centring beam designs. The mechanics of the RFB are first explained, and the equations predicting its responses are given. Two numerical methods are presented for modelling RFBs. The results from a finite element model (FEM) confirmed the sliding behaviour of the RFBs. Then a simplified spring model was created for performing nonlinear dynamic analysis. Finally, a set of steel framed buildings with different heights were designed and computationally subjected to two seismic levels of ground motions. The results suggest that residual interstory drift, peak base shears and peak absolute accelerations can be effectively limited by providing RFBs at the lower storeys. Highlights: A resilient friction beam is proposed using the elastic compression capacity of disc springs. Equations are derived and finite element models are created to investigate the behaviour of the new beam. Seismic responses of moment-resisting frames are analysed after the new beam is provided in the lower storeys.